The positive border effect of EU integration - Steven Brakman; Harry Garretsen; Charles van Marrewijk; Abdella Oumer (Center for Economic Studies and ifo Institute (CESifo), 2011)
Distance related variables typically vary in a cross-section dimension but less so in a time dimension across cities, regions, or countries. The enlargement of the EU or the introduction of the euro, however, can be looked upon as integration shocks that are informative of the consequences of changes in distance over time. Border cities or regions are thought to be more affected by these shocks than more central locations because of the larger impact of changes in the transaction costs that go along with EU integration along the border. Both at the urban and regional level, we find a beneficial influence of the EU integration process as measured by the growth in population share along the integration borders, leading to an extra growth rate of about 0.15 percentage points per annum. The positive integration holds on both sides of the integration border, is active for a limited distance (up to 70km) and time period (up to 30 years), and is particularly important for large cities and regions. Despite the positive EU integration effect, being located along a border remains a burden in view of the (larger) negative general border effect. We do not find similar positive border-integration effects as a result of the introduction of the euro.
Keywords: F15; R12; R23; 330; Europäische Integration; Schock; Grenzgebiet; Regionale Entwicklung; Transaktionskosten; Europäische Wirtschafts- und Währungsunion; Schätzung; EU-Staaten